2012
DOI: 10.3846/13923730.2012.723397
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Optimum Pre-Founded Column System for Top-Down Construction

Abstract: In this work, circular concrete-filled steel tubular (CCFT) columns, rather than the more popular H-shaped columns, were suggested as pre-founded columns for top-down construction. In addition, a novel shear connection system with headed stud shear connectors between the CCFT columns and the flat slabs was developed. It was noted that a CCFT column with a design compressive strength similar to that of an H-shaped column without consideration of length effects can be easily installed, even into a smaller boreho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Based on a bottom-up pile load test, Kim and Mission (2011) presented an improved evaluation of the equivalent load-displacement curve during TDM construction, which indicated that this curve agreed with the measured and simulated top-down curves, as validated in the case studies. In Korea, Rhim et al (2012) developed an optimum pre-formed column system for the TDM. The circular concretefilled tubular steel columns are preferred over the more popular H-shaped columns.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a bottom-up pile load test, Kim and Mission (2011) presented an improved evaluation of the equivalent load-displacement curve during TDM construction, which indicated that this curve agreed with the measured and simulated top-down curves, as validated in the case studies. In Korea, Rhim et al (2012) developed an optimum pre-formed column system for the TDM. The circular concretefilled tubular steel columns are preferred over the more popular H-shaped columns.…”
Section: Introductionmentioning
confidence: 99%
“…Crowded urban areas in Asia have experienced a recent increase in the number of construction sites that employ top-down excavation methods [ 1 ]. Top-down methods are those where the both super and sub-structures are simultaneously built, and they are useful in urban areas where there are strict environmental regulations, lack of working space, and short construction times [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the consideration of the environmental effect of construction is also a big issue, especially in population‐concentrated urban areas, due to existing buildings, roads, and residents. To prevent public nuisance, such as noise, vibration, and dust, during construction, a top‐down construction method is widely used in major Asian cities in Korea, China, Japan, Singapore, and Taiwan . Top‐down construction methods have the advantage of being able to protect nearby buildings as well as underground structures and can thus be applied as an alternative construction method to the conventional bottom‐up construction method.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, H‐shaped steel piles are commonly used as preinstalled columns to support structural load during the top‐down construction process. Even though the preinstalled columns still contain the capacity to support the structural load during the service period of the structure, the bearing capacity of the preinstalled column is usually ignored in the design of the mat foundation (footing) . Due to this, the design of the mat foundation (footing) tends to be conservative, which leads to thicker footing and higher construction costs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation